Alternate wetting and moderate soil drying could increase grain yields in both main and ratoon rice crops. Issue 6 (30th September 2022) - Zhang, Qiang; Liu, Xiangchen; Yu, Guilong; Duan, Bin; Wang, Hao; Zhao, Haiying; Feng, Daqing; Gu, Mengxuan; Hu, Yang; Chen, Yingxia; Liu, Lijun
Abstract: Alternate wetting and drying irrigation is a widely used irrigation method for water‐savings and high‐yielding in rice ( Oryza sativa L.) production; however, its effect on grain yield (GY) in the main and ratoon crops is unclear. With two rice cultivars as materials, the effects on GY in the main and ratoon crop of three irrigation regimes, that is, conventional flooding irrigation (CI), alternate wetting and moderate soil drying irrigation (WMD), and alternate wetting and severe soil drying irrigation (WSD), during grain filling of the main crop were investigated. Compared with CI, WMD increased GY by 6.0∼6.5% in the main crop by increasing the 1, 000‐grain weight and filled grain rate, whereas the ratoon crop GY increased by 13.3∼14.6% via increased panicle number. The WSD had no significant effects on the main crop GY, but significantly decreased ratoon crop GY by decreasing panicle number. A higher leaf photosynthetic rate, leaf area index, root oxidation activity, dry matter accumulation and nonstructural carbohydrate (NSC) translocation under WMD primarily drove the increased 1, 000‐grain weight and filled grain rate in the main crop. Under WMD, higher soluble sugar contents catalysed by high amylase activity and higher zeatin + zeatin riboside in stems of the main crop promoted the growth of regenerated buds and increased the ratoon crop panicle number. In conclusion, WMD during grain filling of the main crop improved the growth and development of the main crop and promote the germination of regenerated buds, thereby increasing the GY of both main and ratoon crops. Core Ideas: Alternate wetting and moderate soil drying irrigation (WMD) increased rice yields in both the main and ratoon seasons. WMD significantly increased ratoon crop yield by increasing its panicle number. WMD increased amylase activity and zeatin + zeatin riboside (Z + ZR) content in stems in the main crop. High soluble sugar and Z + ZR promoted the growth of regenerated buds.